2016
DOI: 10.1038/ncomms13103
|View full text |Cite
|
Sign up to set email alerts
|

NRK1 controls nicotinamide mononucleotide and nicotinamide riboside metabolism in mammalian cells

Abstract: NAD+ is a vital redox cofactor and a substrate required for activity of various enzyme families, including sirtuins and poly(ADP-ribose) polymerases. Supplementation with NAD+ precursors, such as nicotinamide mononucleotide (NMN) or nicotinamide riboside (NR), protects against metabolic disease, neurodegenerative disorders and age-related physiological decline in mammals. Here we show that nicotinamide riboside kinase 1 (NRK1) is necessary and rate-limiting for the use of exogenous NR and NMN for NAD+ synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
445
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(468 citation statements)
references
References 46 publications
22
445
1
Order By: Relevance
“…In fact, the present study demonstrates that a single dose of IP NR injection induced a transient increase in NAD + level (about 3 folds) in lungs of mice, which prevented lung and heart injury, and improved the survival in septic mice. Previous evidence showed that administration of NR effectively elevated NAD + levels in liver and muscle in mice [15,28]. Thus, boosting NAD + with NR may also protect other organs in sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the present study demonstrates that a single dose of IP NR injection induced a transient increase in NAD + level (about 3 folds) in lungs of mice, which prevented lung and heart injury, and improved the survival in septic mice. Previous evidence showed that administration of NR effectively elevated NAD + levels in liver and muscle in mice [15,28]. Thus, boosting NAD + with NR may also protect other organs in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…This is because sepsis induced a rapid reduction of NR kinase 1/2 in lung and liver (data not shown), essential enzymes responsible for conversion of NR to NAD + [14,15]. Although the protection conferred by pretreatment with NR may limit the use of NR as a therapeutic agent for sepsis at this moment, administration of NR can provide a preventive approach for septic organ injury as NR has been widely used as a health supplement [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, we observed increased transcript levels of the muscle-specific nicotinamide riboside kinase 2 (Nmrk2) and decreased transcript levels of nicotinamide phosphoribosyltransferase (Nampt) in FXN-KO hearts. Increased Nmrk2 suggests an enhanced capacity of the FXN-KO heart to take up exogenous NAD + precursors NR and NMN (27), and decreased Nampt suggests reduced de novo synthesis of NAD + in the FXN-KO heart. These observations were validated at the protein level by analysis of the FXN-KO cardiac mitochondrial proteome, which revealed a decrease in the mitochondrial levels of NAMPT and increased expression in the mitochondrial isoform of nicotinamide nucleotide adenylyltransferase 3 (NMNAT3), a protein involved in NMN salvage ( Figure 1, C and D, respectively).…”
Section: Fxn-ko Cardiac Mitochondria Have Protein Hyperacetylation Rmentioning
confidence: 99%